Negotiation of The Ma’rifah Community Identity In Forming Sufistic Sholihan In Seuruway Community of Aceh Tamiang - Mohd. Nasir; Mawardi Mawardi (Jurnal Ushuluddin, 2020)
This article is based on a variety of Seruway Aceh society phenomenon which is separated into two communities. One of them becomes a representative of the majority and the other as a representative of a minority. Ma’rifah community is a minority that got discriminative treatment from the majority one. Nevertheless, this community was able to expand as a majority. The article is aimed at explaining the relation of the Ma’rifah community in forming Sufistic identity in religious social space in Seruwey Aceh and it is aimed at explaining its effect onthe variation of religious practice. The research is the social anthropology of the ethnographic approach. The data were collected through interview, subject for the research was determined by using purposive sampling. The resultsshow that; first, the Ma’rifah community is successful in developing familial relationships, a close friend and using power relations as capital in forming Sufistic habitus. Second, the Ma’rifah community presented an effect on religion variant, it is not only between majority and minority, but Ma’rifah community itself is separated into several communities, a part of Them still in Sufistic ideology which is opposite of majority, and some others negotiate to be part of the majority